Evaluation of Australian Brassica napus genotypes for resistanceto the downy mildew pathogen, Hyaloperonospora parasitica - Ge, Cynthia; Li, H.; Sivasithamparam, K.; Barbetti, M. (CSIRO Publishing, 2008)
Downy mildew, caused by the pathogen Hyaloperonospora parasitica, is a severe disease of oilseed rape(Brassica napus) seedlings in some regions of Australia. Sixty-three cultivars of Australian spring-type oilseed rape wereevaluated for their levels of resistance to five isolates of the downy mildew pathogen, using a cotyledon infection test undercontrolled-environment conditions. A high level of resistance, characterised by the absence of disease symptoms or only theappearance of very sparse sporulation on inoculated cotyledons, was expressed in cvv. Pioneer 45Y77 and Pioneer 46Y78.This is the first study to identify Australian genotypes of oilseed rape highly resistant to H. parasitica. The resistance toH. parasitica identified in this study will not only enable Australian oilseed rape breeders to incorporate resistance toH. parasitica into new cultivars for enhanced resistance to this disease, but will also allow direct deployment of the mosthighly resistant genotypes identified directly in situations and regions most conducive to the development of severe downymildew disease.